Entrepreneurial intention among undergraduate students at Universiti Malaysia Sabah, Labuan International Campus - Mohd Nasir Samsulbahri; Safiah Masbaka; Dayang Nora Asmara Awang Mohamad; Maisyarah Stapah @ Salleh (Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia, 2024)
Amidst Malaysia's notable unemployment challenges, there exists a burgeoning interest in harnessing entrepreneurship as a catalyst for job creation, economic advancement, and individual empowerment. This investigation endeavors to scrutinize the determinants shaping entrepreneurial inclinations among undergraduate students, particularly within the confines of Universiti Malaysia Sabah Labuan International Campus (UMSLIC). Leveraging the framework of the Theory Of Planned Behavior (TPB), this inquiry delves into the entrepreneurial aspirations of undergraduate cohorts, augmented by the incorporation of entrepreneurial self-efficacy and the need for achievement as pertinent variables. Data acquisition was facilitated through an online survey administered to 188 undergraduate participants at UMSLIC, employing a convenience sampling method. Subsequent hypothesis testing was carried out employing SPSS version 27. The outcomes reveal a positive correlation between Entrepreneurial Attitude (EA), Perceived Behavior Control (PBC), Entrepreneurial Self-Efficacy (ESE), and Need for Achievement (NA) with Entrepreneurial Intention (EI) among the targeted demographic. However, Subjective Norm (SN) was observed to bear no significant influence on Entrepreneurial Intention (EI) among undergraduates at UMSLIC. These empirical insights can be instrumental for policymakers in crafting tailored interventions and initiatives aimed at fostering and augmenting student engagement in entrepreneurial pursuits.